(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
The serpentinite is interesting for containing 12–14 weight% of crystal water and is applicable as a filler for the concrete of nuclear reactors. Such a concrete differs by high water content, the most part of which preserves at temperature up to 450℃ during a long work with the concrete. In Armenia the reserves of the serpentinite are connected with ultrabasic rocks of two ophiolitic ranges and are practically inexhaustible. Taking into account the last statement, we suggest to use Armenian serpentinite in protection system of Armenian nuclear reactor.